Strategies for Effective Science Education in the Present Century - Vijayan, C. (JOURNAL OF INDIAN EDUCATION, 2011)
The present century continues to witness several emerging technologies often beyond the wildest of our imaginations. An unlimited content of information is available easily from resources all over the globe, packaged in a variety of extremely effective and unconventional styles of presentation. The shift of emphasis from the textbooks and the blackboard to the internet, virtual classrooms and multimedia is happening at a tremendous pace. The magnitude and speed of the information explosion of the present times re-emphasises the urgent need for building bridges across the huge gaps between information, knowledge and wisdom. This shifts our attention to the very basic purpose of education as an enabling, enriching and empowering technology, demanding focused efforts to evolve innovative strategies addressing the perspectives of the content and the style, the teacher and the taught, the enabling agencies and the public — all stakeholders. The emphasis is shifting towards learning to learn and uncovering and discovering the syllabus. Science education involves inspiring and motivating the student community at large, imparting theoretical as well as practical skills and highlighting the need for creative thinking and innovation. The proclaimed role of the educator, of opening up the students’ eyes (‘chakshurunmeelitam yena’) towards glimpses of the ultimate reality, is particularly significant for science education. It is important to address the fundamental issue of the recent migration of excellent brains from science and science education towards greener pastures. Obviously, these pastures also are to be made sufficiently green! While waiting for this, we have also to evolve strategies within our reach to save the situation. The treasury of experience and wisdom of original thinkers on education and great teachers of the past and the present provides us specific examples, tested ideas and adaptable techniques to start with. We may have to struggle a bit, shaping bricks and polishing stones, which is an integral part of building up a monument. The fruits may be rewarding; but the charm and thrill of the adventure itself are worth the effort!